Utilizing Reading Competitions to Foster Academic Skill Development Among Pesantren Students - Umi Kulsum; Kustiana Arisanti; Ivonne Hafidlatil Kiromi (Al-Qalam Institue, 2026)
This study aims to examine the role of the kitab reading competition at a pesantren in enhancing students' academic skills, including cognitive abilities and self-management. Using a qualitative approach, data was collected through observations and in-depth interviews with caretakers, committee members, and students. The findings reveal that the competition plays a crucial role in transforming the students' learning processes. Unlike traditional classroom settings that sometimes lead to a decline in motivation, the reading competition, with its lottery-based system and reward incentives, encourages students to engage more seriously and holistically with their studies. Students are not only required to memorize texts but also to critically analyze and apply them in everyday life. This competition, therefore, serves as both an evaluation tool and a platform for fostering academic proficiency, intellectual development, and self-directed learning. The study highlights the effectiveness of this approach in improving students' academic skills and motivation in pesantren settings.